2002
DOI: 10.1002/cne.10520
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cholinoceptive glycinergic neurons in the mammalian retina

Abstract: The light-evoked release of acetylcholine (ACh) affects the responses of many retinal ganglion cells, in part via nicotinic acetylcholine receptors (nAChRs). nAChRs that contain beta2alpha3 neuronal nicotinic acetylcholine receptors have been identified and localized in the rabbit retina; these nAChRs are recognized by the monoclonal antibody mAb210. We have examined the expression of beta2alpha3 nAChRs by glycinergic amacrine cells in the rabbit retina and have identified different subpopulations of nicotinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Therefore, this cell forms an inhibitory feedback loop onto starburst cells. Further contribution to this loop may come from nicotinic receptors which have been localized to many classes of glycinergic amacrine cells, including DAPI-3 cells (Zucker and Ehinger, 2001;Dmitrieva, et al, 2003). Neal and Cunningham also found that this loop depends on GABA through GABA B receptors.…”
Section: Inhibitory Feedback Loop In the Cholinergic Circuitrymentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, this cell forms an inhibitory feedback loop onto starburst cells. Further contribution to this loop may come from nicotinic receptors which have been localized to many classes of glycinergic amacrine cells, including DAPI-3 cells (Zucker and Ehinger, 2001;Dmitrieva, et al, 2003). Neal and Cunningham also found that this loop depends on GABA through GABA B receptors.…”
Section: Inhibitory Feedback Loop In the Cholinergic Circuitrymentioning
confidence: 93%
“…The dendritic trees of DAPI-3 cells, which range from about 150 m up to about 300 m, exhibit recurved looping processes, reminiscent of those described for directionally selective ganglion cells (Amthor et al, 1984;Oyster et al, 1993). These bistratified GABA A -receptive amacrine cells express nicotinic acetylcholine receptors (Zucker and Ehinger, 2001;Dmitrieva et al, 2003), and both accumulate glycine (Vaney, 1990;Wright et al, 1997) and are immunoreactive for glycine-transporter proteins (Zucker et al, 1996;Dmitrieva et al, 2003).…”
mentioning
confidence: 94%
“…Colocalization of a7 and a3b2 nAChRs in Rabbit Retinal Neurons Expression of a7 nAChRs by amacrine cells and some cells in the GCL of rabbit retina raised the question whether they colocalize with b2-containing nAChRs present in subsets of amacrine and GCs as well (Keyser et al 2000;Dmitrieva et al 2001Dmitrieva et al ,2003. Simultaneous visualization a3b2 nAChRs labeled by MAb210, and a7 nAChRs revealed that although some cell bodies in the INL and the GCL were positively labeled by both antibodies, dendritic varicosities in the IPL showed no apparent colocalization of two markers, with only a few exceptions (Figures 6D-6F).…”
Section: Expression Of A7 Nachrs By Different Subpopulations Of Bipolmentioning
confidence: 99%
“…Both receptor subtypes are expressed directly by GCs, and nAChRs are expressed by upstream cells as well. Indeed, immunohistochemical (IHC) studies have demonstrated that in rabbit retina many GCs as well as several types of amacrine cells express aBgt-insensitive nAChRs containing b2 subunits, some of which are in combination with a3 and possibly other subunits (Keyser et al 2000;Dmitrieva et al 2001Dmitrieva et al ,2003.…”
mentioning
confidence: 99%
“…In the salamander (Zhang et al, 1997) and turtle (Yu and Eldred, 2005a) glycine and GABA are also known to interact and reciprocally regulate one another in the inner retina. Both acetylcholine (Neal and Cunningham, 1995;Neal et al, 2001;Dmitrieva et al, 2003) and NO (Yu and Eldred, 2005b) have been implicated in influencing each of these inhibitory transmitters.…”
mentioning
confidence: 99%